Maternal Mortality - World Bank (Washington, DC, 2012)
Over 529,000 women die annually from complications during pregnancy, childbirth, or the postpartum period. Nearly all of these deaths occur in developing countries, where fertility rates are higher and a woman's life time risk of dying during pregnancy and childbirth is over 400 times higher than in developed countries. Additionally, an estimated 20 million women endure lifelong disabilities such as pelvic pain, incontinence, obstetric fistula, anemia and infertility. The main direct causes of maternal death are severe bleeding, unsafe abortion, infection, eclampsia, and obstructed labor; the indirect causes include anemia, malaria, heart disease, and HIV. Pregnancy complications are the main cause of death for women aged 15-19. High maternal mortality rates in many countries result from poor reproductive health care, including not having access to skilled care during pregnancy and childbirth and access to safe abortion even where it is legal, especially for the poorest women. Risks of poor outcomes during pregnancy and childbirth are exacerbated by poverty, low status of women, lack of education, poor nutrition, heavy workloads and violence. While many factors contribute to maternal death, one of the most effective means of preventing maternal health is to improve health systems and primary health care to ensure availability of skilled attendance at all levels and access to 24-hour emergency obstetric care. Family planning services could also reduce maternal deaths and morbidities by 30 percent. Prevention of unwanted pregnancies and access to safe abortion as allowed by law and post abortion care services could reduce maternal deaths and injuries caused by unsafe abortions - over 68,000 women die from unsafe abortions annually.